DEPICTION OF HEAVEN FROM THE AL-QUR'AN PERSPECTIVE (ANALYSIS OF AVRAM NOAM CHOMSKY'S DEEP STRUCTURE AND SURFACE STRUCTURE APPROACH) - Muhalil, M. Nurwathani Janhari (el-Umdah, 2023)
Abstract: A serious study of the Qur'?n will lead to the conclusion that there is a dialectical relationship between the Qur'?nic text and the reality of Arab society. In fact, the redaction of the Qur'?nic text itself is largely determined by the reality faced by the Qur'?n. Departing from this background, this study aims to find a dialectical relationship between the depiction of heaven in the Qur'an and the reality of 7th century Arab society by using the surface structure and deep structure approaches initiated by Avram Noam Chomsky. The approach initiated by Chomsky uses psychological analysis as a tool to find the relationship between deep structure and surface structure. The results of this study show that the depiction of heaven in the Qur'an is closely related to geographical and geological factors, as well as the socio-cultural conditions of 7th century Arab society. This is based on the characteristics of the community as a material and sensory society, so that heaven as an abstract thing is illustrated as a thing that can be sensed, and describes the ideal life expected by the Arab community in the 7th century. Keywords: Heaven, Deep Structure and Surface Structure, Avram Noam Chomsky.